2008
DOI: 10.1016/j.ydbio.2008.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Activin/TGFβ and BMP crosstalk determines digit chondrogenesis

Abstract: The progress zone (PZ) is a specialized area at the distal margin of the developing limb where mesodermal cells are kept in proliferation and undifferentiated, allowing limb outgrowth. At stages of digit morphogenesis the PZ cells can undergo two possible fates, either aggregate initiating chondrogenic differentiation to configure the digit blastemas, or to die by apoptosis if they are incorporated in the interdigital mesenchyme. While both processes are controlled by bone morphogenetic proteins (BMPs) the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 62 publications
7
99
0
Order By: Relevance
“…Rather, BMP signaling is required for initial chondrogenesis as outlined above and BMP/pSmad signaling appears to be the driving force for the outgrowth of the digit condensations by means of distally directed chondrogenesis. Montero et al (2008) furthermore showed that the integrity of the DC/ PFR required AER signaling, which links the DC/PFR to the elongation model proposed by Sanz-Ezquerro and Tickle (2003). These studies altogether suggest that the outgrowth of digit condensations depends on a timely and spatially defined input of strong BMP/Smad1/5/8 signaling.…”
Section: Developmental Dynamicssupporting
confidence: 55%
See 2 more Smart Citations
“…Rather, BMP signaling is required for initial chondrogenesis as outlined above and BMP/pSmad signaling appears to be the driving force for the outgrowth of the digit condensations by means of distally directed chondrogenesis. Montero et al (2008) furthermore showed that the integrity of the DC/ PFR required AER signaling, which links the DC/PFR to the elongation model proposed by Sanz-Ezquerro and Tickle (2003). These studies altogether suggest that the outgrowth of digit condensations depends on a timely and spatially defined input of strong BMP/Smad1/5/8 signaling.…”
Section: Developmental Dynamicssupporting
confidence: 55%
“…Two landmark studies have shed light on the molecular mechanisms responsible for this lineage commitment. The labs of Juan Hurle and John Fallon both demonstrated that a population of cells immediately in front of the growing digit condensation, the digit crescent (DC, Montero et al, 2008) or phalanx-forming region (PFR, Suzuki et al, 2008) controlled the incorporation of mesenchymal precursors into the condensation. This population was positive for the BMP receptor BmpR1b and the chondrogenic lineage marker Sox9 and showed high activity of the canonical BMP signaling pathway as it was positive for phosphorylated Smads 1, 5, and 8 (pSmad1/5/8).…”
Section: Elongation Of the Initial Condensation By Distally Directed mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the chick indicates that bone morphogenetic protein (BMP)/pSMAD1/5/8 signaling in a population of cells in front of the growing condensation, referred to as the phalanxforming region (PFR) or digit crescent (3,4), is involved in the elongation of the digital rays. This work suggests that the PFR acts as a signaling center to drive distal elongation of the digit and thus determines the number of phalanges via commitment of distal mesenchymal cells to the cartilage condensation.…”
mentioning
confidence: 99%
“…As with many cell signaling factors, BMPs function's can be regulated along any step of the signaling cascade -either extracellularly, at the cell membrane or intracellularly (Montero, et al, 2008). One such regulation method is another family of cytokines referred to as bone morphogenetic protein antagonists, examples of which include noggin, gremlin, follistatin, and sclerostin.…”
Section: Bone Morphogenetic Proteins and Bone Morphogenetic Protein Amentioning
confidence: 99%